Penguatan Softskill Guru Dalam Upaya Peningkatan Etos Belajar Peserta Didik Pada Masa PAndemi Covid-19 - Muhamad Ridwan Effendi; Suci Nurparatiwi; Sari Narulita; Dziyaning Farihani Tsaqila; Muh. Nurhidayat (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
The low learning ethic of the participants in the learning process who was brave throughout the Covid-19 pandemic was shown by the attitude of students who did not appreciate the learning process, even they had fun in their world (such as playing games, streaming Youtube, sleeping, travelling) without a teacher. Who is explaining the material. No, this problem is also experienced by teachers at the Nurul Huda Islamic boarding school, Bekasi, where they develop their capacity as teachers in an active, innovative, creative, fun, happy and meaningful (Paikem Gembrot) learning process and increase the learning ethos of students through the use of learning media. Based on this, the community service activity of the community partnership program (PPM PkM) provides soft skills support for teachers through learning media development activities through 1) training and assistance in developing Hot Potatoes learning media for teachers to provide soft skills strengthening in its efforts to improve student's learning ethos ; (2) implementing mentoring for teachers to find out their understanding of the material presented; (3) provide a forum for teachers to develop learning models and approaches that can support the improvement of students' learning ethos.